Masonry (Wheels of learning, 1996)
This volume was developed by the National Center for Construction Education and Research (NCCER) in response to the training needs of the construction, maintenance, and pipeline industries. Masons build structures of masonry units. Masonry units are blocks of brick, concrete, ashlar, glass, tile, adobe, and other materials. In the most common forms of masonry, a mason assembles walls and other structures of clay brick or concrete masonry units (CMUs) using mortar to bond the units together